Radiological and Functional Outcomes of Conservatively Managed Osteoporotic Vertebral Fractures at the Thoracolumbar Junction: A cross sectional study - Acharya, Shankar; Thapa, Jagadish; Chahal, Rupinder Singh; Kalra, Kashmiri Lal; Kaucha, Deepak (Biomedical Sciences and Clinical Medicine, 2023)
OBJECTIVE This study examined how osteoporotic vertebral fracture (OVF) patients treated conservatively at a multi-specialty hospital were progressing clinically and radiologically. METHODS This cross sectional, observational study was conducted at Sir Ganga Ram Hospital, New Delhi, India during the period of July 2021 to October 2021. Cases with at least a 6-month follow-up were evaluated. VAS pain score, Oswestry Disability Index (ODI), and local kyphotic angle (COBB’s angle) at the time of fracture and at the latest follow-up were recorded and analyzed. RESULTS There were 30 patients (female: male = 2.75:1) with a mean age of 67.37 years (45-85). The average VAS score at the time of fracture was 8 (6 to 10) and at the time of final follow-up was 2 (1 to 6) (p = 0.001). The average ODI score at the time of fracture was 44 (35 to 62) and at the time of final follow up was 5 (4 to 40) (p = 0.001). The average Cobb’s angle at the time of fracture was 14.31o and at the final follow up was 15.66o (p = 0.011). CONCLUSIONS Conservative management of OVF can lead to an increase in the local kyphotic angle. The fact that the patients experienced significant decreases in VAS pain scores and ODI scores by the final follow-up leads to the conclusion that patients can have a good quality of life even with conservative management of osteoporotic vertebral fractures.